2021
DOI: 10.1101/2021.09.28.462065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beneficial Effects of Celastrol on Immune Balance by Modulating Gut Microbiota in Dextran Sodium Sulfate-Induced Ulcerative Colitis

Abstract: Ulcerative colitis (UC) is a chronic inflammatory bowel disease caused by multi-factors including colonic inflammation and microbiota dysbiosis. Previous studies have indicated that Celastrol (CSR) has strong anti-inflammatory and immune-inhibitory effects. Here, we investigated the effects of CSR on colonic inflammation and the mucosal immunity in an experimental colitis model, and addressed the mechanism by which CSR preforms the protective effect. We characterized the therapeutic effects and the potential m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Lima et al identified the speices Odoribacter splanchnicus, which plays a key role in FMT, by performing the immune response use omic analysis in donor and recipient fecal samples (pre-and post-intervention), Further through mouse experiments, they proved that Odoribacter splanchnicus is the key bacterium (Lima et al, 2021). Similarly, Li et al treated a mouse model of DSS-induced colitis with FMT in combination with a 16S rRNA analysis, revealing that FMT ultimately alleviates colitis by regulating the flora (Li et al, 2021a). Generally, in all of these analyses, the changes in metagenome-based strategy include 16S rRNA sequencing of total bacteria DNA were observed, while changes in the live bacteria DNA were neglected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lima et al identified the speices Odoribacter splanchnicus, which plays a key role in FMT, by performing the immune response use omic analysis in donor and recipient fecal samples (pre-and post-intervention), Further through mouse experiments, they proved that Odoribacter splanchnicus is the key bacterium (Lima et al, 2021). Similarly, Li et al treated a mouse model of DSS-induced colitis with FMT in combination with a 16S rRNA analysis, revealing that FMT ultimately alleviates colitis by regulating the flora (Li et al, 2021a). Generally, in all of these analyses, the changes in metagenome-based strategy include 16S rRNA sequencing of total bacteria DNA were observed, while changes in the live bacteria DNA were neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Li et al. treated a mouse model of DSS-induced colitis with FMT in combination with a 16S rRNA analysis, revealing that FMT ultimately alleviates colitis by regulating the flora ( Li et al., 2021a ). Generally, in all of these analyses, the changes in metagenome-based strategy include 16S rRNA sequencing of total bacteria DNA were observed, while changes in the live bacteria DNA were neglected.…”
Section: Introductionmentioning
confidence: 99%